Bacterial Amylase Production and its Application as a Detergent Additive: Significance of Industrial Enzyme (Biological Sciences - PJSIR, 2025)
Microbial amylase is one of the most significant industrial enzymes utilized in the brewing, baking, washing and textile sectors. In the current study, the rhizospheric soil micro-organisms were examined for their capacity to produce amylase and effort made to isolate thermostable amylase enzymes that could be employed as a detergent addition and stable at high pH levels. Banana, Neem and Pomegranate plant soil rhizospheres which is yielded a total of 84 bacterial isolates. Out of these, 21% of the bacteria produce the amylase. In the investigation, Bacillus made up the bulk of the isolates. Additionally, the amylase activity measured at different media pH and temperatures and isolated from Bacillus showed great stability at alkaline pH and thermal stability upto 60 °C and might be used as a detergent component in the detergent industry. They also had a high potential for removing starch stains.